Asuhan Keperawatan Keluarga Pada Tahap Perkembangan Pelepasan Dengan Pemberian Intervensi Senam Hipertensi Untuk Menurunkan Tekanan Darah Pada Ny K - Riyana Vini Alvionita; Alfika Safitri; Rina Puspita Sari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Families with adult children or discharge are the stages that begin when the first child leaves the house. Hypertension is a condition in which a person experiences an increase in blood pressure above normal which can result in morbidity and mortality. The estimated number of cases of hypertension in Indonesia is 63.309.620 people, while the death rate in Indonesia due to hypertension is 427.218 deaths. Hypertension gymnastics is a sport that one of the aims is to increase blood flow and oxygen supply to the active muscles and skeleton, especially to the heart muscle, so that it can help reduce blood pressure in people with hypertension. Objective: to determine the effect of hypertension exercise to reduce blood pressure in hypertensive patients. Method: by way of interviews and nursing care. Results: The case study was obtained after the client was given hypertension exercise therapy to reduce blood pressure in Mrs. K with significant results, where there was a decrease in blood pressure from 184/94mmHg to 140/80mmHg. Conclusion: Hypertension exercise has an effect on reducing blood pressure in hypertensive patients.